PERANCANGAN ALAT PEMINDAH MASAKAN YANG AMAN : KAJIAN MATERIAL - Yeny Pusvyta; Reny Afriany (TEKNIKA: Jurnal Teknik, 2014)
ABSTRACT In designing a prototype of a transporter cuisine, study material at the prototype is very necessary because the material contact with the hot oil is a medium for frying food. This study was conducted to find out whether the material used was food grade, by examining the properties of materials that make up the components of the tool. Selection of material with the chart Melting point in ceramic , metal and polymer and Bubble charts strength vs. maximum service temperature gives an overview of where the material that may be used which is in food grade criteria and should not be used so that users of such tools is not compromised health . Keywords: prototype of a transporter cuisine, material, food grade